China-North Korea relations: at a crossroad or same old, same old. Issue 3 (8th July 2019) - Kim, Young Joon
Abstract : Purpose: The purpose of this paper is to examine the nature of the China–North Korea alliance that has been often described as "Lips and Teeth" or "Blood Tied." Design/methodology/approach: In order to make accurate assessment of the China–North Korea relations, this paper conducts indepth historical analysis of the relations. The relations between two countries were formed in 1940s and lasts until today. Findings: However, by looking into the history of two countries, this paper argues that the bilateral relations are not an extraordinary but an ordinary state-to-state relations dictated by national interests. Changes in their calculus of national interests affect their relations. They cooperate with each other when they see mutual benefit in doing so and tension arises when there is a conflict of interests. What should be noted is that the changes in the nature of relations is different from the deterioration in the relations. Recent improvement of their relations supports this paper's argument. Originality/value: This paper suggests new look at the China–North Korea relations that has been considered as an extraordinary relations. The findings of this paper suggest that the alliance relation is not different from other state-to-state relations where conflict and cooperation occurs based on their national interests.